Socratic Dialogue Model in Developing PAI Learning at SMK Darut Taqwa Purwosari - Abd Mukhit Karomi; Ahmad Ma'ruf (Al-Makki Publisher, 2026)
This study aims to analyze the implementation of the Socrates dialogue model in developing Islamic Religious Education (PAI) learning at SMK Darut Taqwa Purwosari. The Socrates dialogue model is a learning approach that emphasizes a critical, reflective, and in-depth process of questioning and answering to improve students' understanding of the learning material. Prior to this study, the development of PAI learning at this school still faced a gap in the internalisation of values, as varied methods had not been systematically linked to a critical-reasoning process. This research employs a qualitative approach through the Classroom Action Research (CAR) method, conducted in two cycles, each comprising the stages of planning, action, observation, and reflection. Data collection techniques include observation, interviews, and documentation. The results of the study show that the application of the Socrates dialogue model in PAI learning is able to increase student participation, critical thinking skills, confidence in expressing opinions, and a deeper understanding of Islamic values. In addition, this model helps to create an interactive and communicative learning atmosphere between teachers and students. The obstacles faced in its implementation include differences in students' thinking skills, limited study time, and lack of readiness of some students to actively participate in discussions. Therefore, an effective mentoring and classroom management strategy is needed so that the Socrates dialogue model can be optimally applied in PAI learning. This research is expected to be a reference for educators in developing innovative and student-centered learning methods.